Regeneration of Syzygium myrtifolium walp. from seed fragments – evidence of polyembryony? - Fui, Ying Tsan (Penerbit Universiti Kebangsaan Malaysia, 2023)
Intact Syzygium myrtifolium seed produces a single seedling although most species within the same genus are polyembryonic. Following the earlier work that found the potential of more than one plantlet development from the fractionated seeds of some monoembryonic Eugenia spp. belonging to the same family, the present work assessed the sprouting of S. myrtifolium seed fractions on moistened paper towel pads. This study was carried out in the enclosed plastic boxes at ambient temperature in the laboratory. The results obtained indicated that the different parts of the cotyledons could develop plantlets spontaneously following incision of a seed into separated fractions. Despite the reduced mass, the seed fragments revealed the potential of developing more than one plantlet in vivo from a seed. Injury or seed incision has been suggested to trigger the development of embryonic cell in the cotyledon leading to the formation of an entire plant in contrast to polarity committed by whole seed. For the fragmented seeds that did not regenerate full plants, more than 80% of them exhibited unsynchronized adventitious root development. In the re-growth evaluation, more than 70% of the seed fragments formed new adventitious roots on the new cotyledonary surfaces after the removal of plantlets and the attached cotyledons. This phenomenon suggests the spread of meristematic tissues within the cotyledons. Future work should look into the intrinsic signals and external cues that regulate the cellular differentiation and development in the seed fractions in revealing the polyembryony in S. myrtifolium.